2007
DOI: 10.2224/sbp.2007.35.9.1279
|View full text |Cite
|
Sign up to set email alerts
|

Treating Stress-Related Pain in a Clinical Sample With Flotation-Rest: A Further Report on Improvements in Pain Assessed by the Pain Area Inventory (Pai)

Abstract: Thirty-two patients (29 women and 3 men) with stress-related ailments were recruited through the Community Health Care Centre in the city of Lidköping, Sweden. The mean age was 47.75 years (SD = 8.30).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Although floatation-REST conferred no benefit for structural damage or muscular performance in this study, the reduced sensory environment led to significant attenuation of muscle soreness in the first 48 h of exercise recovery. Floatation-REST has consistently demonstrated efficacy as a pain management intervention outside of exercise recovery, with several studies revealing significant improvements in pain symptomology compared with nontreatment controls (41)(42)(43)(44). Many of these investigations involved patient populations experiencing stress-related muscle tension and pain while using a more conventional floatation-REST treatment scheme of 2-3 sessions a week for up to 6 wk.…”
Section: Discussionmentioning
confidence: 99%
“…Although floatation-REST conferred no benefit for structural damage or muscular performance in this study, the reduced sensory environment led to significant attenuation of muscle soreness in the first 48 h of exercise recovery. Floatation-REST has consistently demonstrated efficacy as a pain management intervention outside of exercise recovery, with several studies revealing significant improvements in pain symptomology compared with nontreatment controls (41)(42)(43)(44). Many of these investigations involved patient populations experiencing stress-related muscle tension and pain while using a more conventional floatation-REST treatment scheme of 2-3 sessions a week for up to 6 wk.…”
Section: Discussionmentioning
confidence: 99%
“…The test consists of two anatomical images of a human being, one frontal and one dorsal. 13,24 The task of the participants was to indicate with a color pen their areas of pain. This test was given both before and after the treatment period.…”
Section: Pain Area Inventorymentioning
confidence: 99%
“…Flotation-REST has been scientifically investigated and is today considered a well-developed and scientifically proved method used to reduce stress, depression, anxiety, and to increase optimism and sleep quality [ 15 – 17 ]. Significant pain reduction has also been reported after using flotation-REST technique [ 18 , 19 ]. A meta-analysis by Dierendonck and Nijenhuis [ 20 ] concluded that flotation-REST has positive effects on physiology (e.g., lower levels of cortisol, lower blood pressure and well-being).…”
Section: Introductionmentioning
confidence: 99%